Efficacy of tiotropium in treating patients with moderate-to-severe asthma: A meta-analysis and systematic review based on 14 randomized controlled trials - Meng, Jian-Feng (Medicine (Baltimore), 2019)
BACKGROUND: The goal of the current meta-analysis and systematic review was to explore the efficacy of tiotropium in treating patients with moderate-to-severe asthma on the basis of qualified randomized controlled trials (RCTs). METHODS: The following online electronic databases, such as Cochrane, PubMed, and Embase database were screened to identify qualified studies updated to January 2019 through the use of index words. Several literatures that were relevant to the present analysis were also included. To further analyze the main outcomes, we utilized the odds rations (OR), and mean difference (MD) along with its 95% confidence interval (95% CI). RESULTS: A total of 14 RCTs with 4998 patients in the tiotropium group and 5074 patients in the control group were included in the present study. On the basis of the pooled results, tiotropium was significantly associated with improved morning PEF (SMD: 3.29, 95%CI: 2.03–4.55), evening PEF (SMD: 3.36, 95%CI: 2.24–4.48), peak FEV (SMD: 2.67, 95%CI: 1.47–3.88), and trough FEV (SMD: 1.90, 95%CI: 0.87–2.92) vs the control group. Nevertheless, no significant difference was observed in peak FVC (SMD: 0.77, 95%CI: −0.21–1.76), trough FVC (SMD: 0.67, 95%CI: −0.18–1.53), AE (RR: 0.98, 95%CI: 0.94–1.02) and serious AE (RR: 1.08, 95%CI: 0.77–1.52) between the 2 groups. CONCLUSIONS: In this review, we summarized the significant effect of tiotropium for the treatment of moderate-to-severe asthma, mainly in increasing morning PEF, evening PEF, peak FEV and trough FEV based on high-quality RCTs. Nevertheless, no significant difference in peak FVC, trough FVC, AE and serious AE was found between the 2 groups. A close comparison of the 2 groups revealed that more high-quality larger-sample RCTs are needed to gather more strong evidence on the therapeutic efficacy and safety of tiotropium for clinical practice.